2011
DOI: 10.3390/md10010020
|View full text |Cite
|
Sign up to set email alerts
|

A Chronic Oral Toxicity Study of Marine Collagen Peptides Preparation from Chum Salmon (Oncorhynchus keta) Skin Using Sprague-Dawley Rat

Abstract: Due to the increased consumption of marine collagen peptides preparation (MCP) as ingredients in functional foods and pharmaceuticals, it was necessary to carry out safety requirements in the form of an oral chronic toxicity assessment. In order to define the oral chronic toxicity of MCP, a 24-month feeding study of MCP was carried out. Sprague-Dawley (S-D) rats at the age of four-week of both sexes were treated with MCP at the diet concentrations of 0%, 2.25%, 4.5%, 9% and 18% (wt/wt). The actual food intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…Despite the fact that there are no previous reports available on the hepato-toxicity induced by oral inoculation of food-derived collagen [20], our records have demonstrated histopathological alterations in liver after 30 days of collagen feeding. Similarly, Woo et al, have been mentioned that the collagen-fed mice had a lower level of hepatic Triglyceride; which was consistent with liver histological results.…”
Section: Discussioncontrasting
confidence: 81%
“…Despite the fact that there are no previous reports available on the hepato-toxicity induced by oral inoculation of food-derived collagen [20], our records have demonstrated histopathological alterations in liver after 30 days of collagen feeding. Similarly, Woo et al, have been mentioned that the collagen-fed mice had a lower level of hepatic Triglyceride; which was consistent with liver histological results.…”
Section: Discussioncontrasting
confidence: 81%
“…MCPs are low-molecular-weight peptides extracted from collagen tissues of marine fish, including skin, bone and scales, which account for 30% of marine fish processing waste ( 36 ). Previous investigations have confirmed that these protein fragments are safe in animals and humans ( 24 ). We previously tested the therapeutic effects of MCPs in diabetic animals ( 13 ) and patients ( 10 , 12 , 21 ).…”
Section: Discussionmentioning
confidence: 71%
“…At 1–2 weeks later, fasting blood glucose (FBG) of rats were detected by a blood glucose meter, and 45 rats with FBG levels ≥11.1 mmol/l were considered as T2DM and were used for the experiment. A total of 40 of these diabetic rats were then assigned randomly to 4 groups treated with vehicle (group D), or 2.25 (low dose, group L), 4.5 (medium dose, group M) or 9.0 (high dose, group H) g/kg BW/day MCPs (n=10/group) ( 24 ). The MCPs and vehicle (distilled water; total volume was 1 ml/application) were administered intragastrically every morning after the T2DM model had been established for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental design and T2DM rat model T2DM was induced according to methods described in our previous study (Srinivasan et al 2005). After 2 weeks of HCHFD feeding, freshly prepared streptozotocin [STZ, 30 mg/kg body weight (BW)] in citrate buffer (0.1 M, pH 4.5) was administered intraperitoneally three times a week (Liang et al 2012). At approximately 2 weeks following STZ, fasting blood glucose (FBG) levels were measured using a blood glucose meter (Oxidase methods, OneTouch Ultra; Lifescan, Wayne, PA, USA).…”
Section: Rat Model Of T2dmmentioning
confidence: 99%
“…Of the 50 rats, 45 rats were considered to have T2DM with an FBG level C11.1 mmol/l. Forty of these diabetic rats were then randomly assigned to four groups: vehicle (group D, n = 10), low dose MCPs (2.25 g/kg/day; group L, n = 10), medium dose MCPs (4.5 g/kg/day, group M, n = 10), or high dose MCPs (9.0 g/kg/day, group H, n = 10) (Liang et al 2012).…”
Section: Rat Model Of T2dmmentioning
confidence: 99%